2010
DOI: 10.1111/j.1477-2574.2010.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatectomy risk calculator: an ACS-NSQIP resource

Abstract: The ACS-NSQIP 'Pancreatectomy Risk Calculator' employs 10 easily assessable clinical parameters to assist patients and surgeons in making an informed decision regarding the risks and benefits of undergoing pancreatic resection. A risk calculator based on this prototype will become available in the future as on online ACS-NSQIP resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
134
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(138 citation statements)
references
References 35 publications
4
134
0
Order By: Relevance
“…However, morbidity was still high at 41.56%, and it was not excellent compared with that reported in other institutional or national reports 2, 3, 4, 13. A PF remained the leading cause of total complications; in particular, a PF with an ISGPF grade C was associated with 76.47% of all C–D grades IV–V complications and it significantly resulted in the occurrence of a serious morbidity.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, morbidity was still high at 41.56%, and it was not excellent compared with that reported in other institutional or national reports 2, 3, 4, 13. A PF remained the leading cause of total complications; in particular, a PF with an ISGPF grade C was associated with 76.47% of all C–D grades IV–V complications and it significantly resulted in the occurrence of a serious morbidity.…”
Section: Discussionmentioning
confidence: 66%
“…For the 17,564 patients undergoing PD recorded in the NCD, the 30‐day and in‐hospital mortality rates after PD were extremely low at 1.31% and 2.88%, respectively, which were much better than those of other national cohort‐based reports 12, 13, 14. However, morbidity was still high at 41.56%, and it was not excellent compared with that reported in other institutional or national reports 2, 3, 4, 13.…”
Section: Discussionmentioning
confidence: 84%
“…Most previous outcome studies have grouped patients' diagnoses by benign and malignant disease categories; [17][18][19] this categorization scheme may not be the best method to assess risk and predict outcomes because it does not consider gland size or texture. A recent study from our institution has shown that stratifying patients by diagnosis (and, thus, gland size and texture) can predict risk for postoperative complications in patients of all ages presenting for PD.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one‐third of pancreatectomy volumes in the USA comprises patients who have distal pancreatectomy rather than pancreaticoduodenectomy, and these patients have a significantly lower risk of morbidity and mortality38. The present analysis was limited to patients with highest expected perioperative mortality rate, including only patients with complex HPB resections and total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%